Search for the Standard Model Higgs boson in the decay channel H → ZZ(∗) → 4ℓ with 4.8 fb-1 of pp collision data at √s = 7 TeV with ATLAS - Anduaga, Xabier Sebastián (2012)
This Letter presents a search for the Standard Model Higgs boson in the decay channel H → ZZ(∗) → ℓ+ℓ-ℓ'+ℓ'-, where ℓ,ℓ' =e or μ, using proton–proton collisions at √s = 7 TeV recorded with the ATLAS detector and corresponding to an integrated luminosity of 4.8 fb-1. The four-lepton invariant mass distribution is compared with Standard Model background expectations to derive upper limits on the cross section of a Standard Model Higgs boson with a mass between 110 GeV and 600 GeV. The mass ranges 134–156 GeV, 182–233 GeV, 256–265 GeV and 268–415 GeV are excluded at the 95% confidence level. The largest upward deviations from the background-only hypothesis are observed for Higgs boson masses of 125 GeV, 244 GeV and 500 GeV with local significances of 2.1, 2.2 and 2.1 standard deviations, respectively. Once the look-elsewhere effect is considered, none of these excesses are significant.